Identification of Putative Cytoskeletal Protein Homologues in the Protozoan Host Hartmannella vermiformis as Substrates for Induced Tyrosine Phosphatase Activity upon Attachment to the Legionnaires' Disease Bacterium, Legionella pneumophila - Venkataraman, Chandrasekar (The Rockefeller University Press, 1998)

(untitled)
The Legionnaires' disease bacterium, Legionella pneumophila, is a facultative intracellular pathogen that invades and replicates within two evolutionarily distant hosts, free living protozoa and mammalian cells. Invasion and intracellular replication within protozoa are thought to be major factors in the transmission of Legionnaires' disease. We have recently reported the identification of a galactose/N-acetyl-d-galactosamine (Gal/GalNAc) lectin in the protozoan host Hartmannella vermiformis as a receptor for attachment and invasion by L. pneumophila (Venkataraman, C., B.J. Haack, S. Bondada, and Y.A. Kwaik. 1997. J. Exp. Med. 186:537–547). In this report, we extended our studies to the effects of bacterial attachment and invasion on the cytoskeletal proteins of H. vermiformis. We first identified the presence of many protozoan cytoskeletal proteins that were putative homologues to their mammalian counterparts, including actin, pp125(FAK), paxillin, and vinculin, all of which were basally tyrosine phosphorylated in resting H. vermiformis. In addition to L. pneumophila–induced tyrosine dephosphorylation of the lectin, bacterial attachment and invasion was associated with tyrosine dephosphorylation of paxillin, pp125(FAK), and vinculin, whereas actin was minimally affected. Inhibition of bacterial attachment to H. vermiformis by Gal or GalNAc monomers blocked bacteria-induced tyrosine dephosphorylation of detergent-insoluble proteins. In contrast, inhibition of bacterial invasion but not attachment failed to block bacteria-induced tyrosine dephosphorylation of H. vermiformis proteins. This was further supported by the observation that 10 mutants of L. pneumophila that were defective in invasion of H. vermiformis were capable of inducing tyrosine dephosphorylation of H. vermiformis proteins. Entry of L. pneumophila into H. vermiformis was predominantly mediated by noncoated receptor-mediated endocytosis (93%) but coiling phagocytosis was infrequently observed (7%). We conclude that attachment but not invasion by L. pneumophila into H. vermiformis was sufficient and essential to induce protein tyrosine dephosphorylation in H. vermiformis. These manipulations of host cell processes were associated with, or followed by, entry of the bacteria by a noncoated receptor-mediated endocytosis. A model for attachment and entry of L. pneumophila into H. vermiformis is proposed.